Tibiotalocalcaneal arthrodesis through retrograde nailing for the treatment of juxtaarticular distal tibia aseptic non-unions: A retrospective study at a minimum follow-up of 4 years. Issue 6 (June 2020) - Mosca, Massimiliano; Caravelli, Silvio; Fuiano, Mario; Massimi, Simone; Censoni, Davide; Grassi, Alberto; Vocale, Emanuele; Ceccarelli, Francesco; Zaffagnini, Stefano
Highlights: Aseptic non-union represents a frightening complication of distal tibia fractures, often characterized by a challenging treatment and unsatisfactory results because of the reduced size of the distal bony fragment, diffuse osteoporosis, deformity, bone loss and joint stiffness. The purpose of this study is to determine the efficacy of tibiotalocalcaneal arthrodesis with reamed intramedullary nail as salvage treatment of the nonunions of the distal tibia, presenting mild to severe malalignment and bone stock loss, associated with advanced osteoarthritis of ankle and subtalar joints. Surgical treatment is decided based on various factors, as the type of fracture, the condition of the skin, comorbidities of the patient, the risk of infection. When distal tibia juxta–articular nonunion occurs with simultaneous ankle–hindfoot articular degeneration, association of nonunion revision and arthrodesis can be an effective alternative to other joint-preserving procedure. Abstract: Introduction: The purpose of this study is to determine the efficacy of tibiotalocalcaneal arthrodesis by reamed intramedullary nail in the management of the distal tibia non-unions, associated with end-stage osteoarthritis of ankle and subtalar joints. Materials and methods: 8 patients with radiographical and clinical diagnosis of non-union of the distal tibia have been treated with tibiotalocalcaneal arthrodesis by intramedullary retrograde nail and were retrospectively evaluated. Patients were radiographically and clinically evaluated preoperatively and at final follow-up regarding: satisfaction, AOFAS, VAS. Surgical technique is described. Results: Mean follow-up was 69.2 ± 23.2 months (range 48–108). In terms of subjective outcome, patients reported a highly satisfying result. All patients returned to daily activities, with an average time of 24.7 ± 8.7 weeks. 6 patients could return to their previous work activity, with an average time of 23.6 ± 6.3 weeks. Conclusions: The procedure showed good results at final follow up. Consolidation was achieved in all the treated cases. Considering AOFAS and VAS scores at final follow-up, there was an evident improvement of the conditions of the patients.